2015
DOI: 10.1095/biolreprod.114.119495
|View full text |Cite
|
Sign up to set email alerts
|

Dexrazoxane Abrogates Acute Doxorubicin Toxicity in Marmoset Ovary1

Abstract: Preservation of ovarian function following chemotherapy for nonovarian cancers is a formidable challenge. For prepubescent girls, the only option to prevent chemotherapy damage to the ovary is ovarian tissue cryopreservation, an experimental procedure requiring invasive surgeries to harvest and reimplant tissue, which carries the risk of cancer reintroduction. Drugs that block the primary mechanism of chemotherapy insult, such as dexrazoxane (Dexra) in the context of anthracycline chemotherapy, provide a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Even in countries with such access, the delay in oncologic care and perhaps the lack of counseling regarding fertility preservation options result in many girls and women having irreparable damage to their ovary. Recently, Salih et al reported that Dexra (dexarazoxane), an inhibitor of topoisomerase 2, protects the ovary from doxorubicin by preventing DNA damage [50]. However, currently no medications are approved by the Federal Drug Administration to provide undisputed protection to the ovary from gonadotoxic agents routinely used in chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Even in countries with such access, the delay in oncologic care and perhaps the lack of counseling regarding fertility preservation options result in many girls and women having irreparable damage to their ovary. Recently, Salih et al reported that Dexra (dexarazoxane), an inhibitor of topoisomerase 2, protects the ovary from doxorubicin by preventing DNA damage [50]. However, currently no medications are approved by the Federal Drug Administration to provide undisputed protection to the ovary from gonadotoxic agents routinely used in chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a proof-of-concept study using immortalized KK-15 mouse granulosa cells, we demonstrated that Dexra protects granulosa cells from DXR-induced DNA damage and cytotoxicity in vitro in a manner consistent with inhibiting TOPII DNA cleavage, rather than oxidative stress [ 23 ]. Furthermore, Dexra treatment of in vitro- cultured mouse and marmoset ovaries prior to DXR administration reduced the number of dsDNA breaks, and rescued primary granulosa cell viability [ 23 , 24 ]. The data demonstrated the potential for Dexra to be an effective ovoprotective agent against DXR toxicity by blocking the initial insult as well as subsequent cellular demise.…”
Section: Introductionmentioning
confidence: 99%
“…Great strides have been made through in vitro culture of ovarian cells and tissue pieces/slices [ 32 , 35 , 36 ]. These culture methods have long been a very useful tool for studying reproductive functioning and toxicology.…”
Section: Discussionmentioning
confidence: 99%